1993
DOI: 10.1002/ijc.2910550603
|View full text |Cite
|
Sign up to set email alerts
|

Breath hydrogen and methane in populations at different risk for colon cancer

Abstract: Results from laboratory and clinical studies have suggested that fermentation in the large bowel may play a protective role against colon cancer. Hydrogen and methane are end-products of colonic fermentation that are absorbed into the bloodstream and excreted via expired air in the breath. Thus, breath levels of hydrogen and methane have been used as markers for this process. Breath levels of these gases were compared among 10 ethnic and sex groups that exhibit marked differences for colon cancer risk in Hawai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Interestingly, these four populations are at different risks for bowel cancer and other colonic diseases, but no correlation between these risks and the methane production was observed [ 71 ]. Likewise, another study showed, that Hawaiians and Caucasians produce more colonic methane than three different Asian groups, but again these differences did not correlate with risk of colon cancer among these ethnic populations [ 72 ]. In a more recent study, also motivated by the existing differential risk for colorectal cancer among ethnic groups, genetic fingerprint analysis ( i.e ., terminal restriction fragment length analysis) revealed significantly different types of methanogens in native Africans, African Americans and European Americans [ 73 ].…”
Section: Are There Yet More Archaea Awaiting Detection In Humans?mentioning
confidence: 99%
“…Interestingly, these four populations are at different risks for bowel cancer and other colonic diseases, but no correlation between these risks and the methane production was observed [ 71 ]. Likewise, another study showed, that Hawaiians and Caucasians produce more colonic methane than three different Asian groups, but again these differences did not correlate with risk of colon cancer among these ethnic populations [ 72 ]. In a more recent study, also motivated by the existing differential risk for colorectal cancer among ethnic groups, genetic fingerprint analysis ( i.e ., terminal restriction fragment length analysis) revealed significantly different types of methanogens in native Africans, African Americans and European Americans [ 73 ].…”
Section: Are There Yet More Archaea Awaiting Detection In Humans?mentioning
confidence: 99%
“…Sensor 10 is sensitive to nitric oxide, which is associated with bronchiectasis, airway inflammation, and chronic obstructive pulmonary diseases (COPD) [24][25][26][27]. Finally, Sensor 12 is sensitive to hydrogen, which is used to detect gastrointestinal diseases [28,29]. These sensors are not specially sensitive to acetone, but they are useful when detecting the complications of diabetes.…”
Section: Chemical Sensor Arraymentioning
confidence: 98%
“…In China, the special diet recommended for diabetics features large amounts of fermentable dietary fiber, which leads to colonic fermentation of indigestible carbohydrates [28]. One product of colonic fermentation is hydrogen [29]. It is absorbed into the bloodstream and excreted through the breath.…”
Section: Breath Samplesmentioning
confidence: 99%
“…Sensor 10 is sensitive to nitric oxide, which is associated with bronchiectasis, airway inflammation, and chronic obstructive pulmonary diseases (COPD) [11]- [14]. Finally, Sensor 12 is sensitive to hydrogen, which is used to detect gastrointestinal diseases [15], [16]. A fundamental design concept for the array of sensors used in the system is that each sensor should have a different sensitivity profile over a range of compounds expected in the target application, e.g., the detection of an unknown disease.…”
Section: Breath Samples Acquisitionmentioning
confidence: 99%